Turfgrass Herbicides: Mechanisms of Action and Resistance Management - Ramon G. Leon; J. Bryan Unruh (EDIS)
Herbicides are an effective tool for controlling weeds in turfgrass; however, weeds can become resistant to herbicides and create significant problems for turfgrass production. The best way to combat herbicide resistance is to rotate herbicides with different mechanisms of action (MOA) because using herbicides with different MOAs makes it more likely that weeds resistant to one herbicide will encounter an herbicide to which they are not resistant. This 4-page fact sheet focuses on how to create an herbicide program that uses different MOAs to manage resistant weeds. Written by Ramon G. Leon and Bryan Unruh, and published by the UF Department of Agronomy, August 2015.